Design Guideline for Cultural Learning Center in Historical Area (Thonburi): Adaptive Re-use Old Architecture and Infill Design - Ampaiphan, Tawat (Journal of Architectural/Planning Research and Studies (JARS), 2018)
The objectives of this study are 1) To study about design guideline for cultural learning center in historical area (Thonburi) in characteristic of adaptive re-use old architecture and infill design by choosing three old buildings which have continued in three periods. The first is Ban Bang Yee Khan building or Rachakarun School building which was built during the reign of King Rama V and VI. The second is administrator office of Sura Bang Yee Khan factory which was built in Colonial Style. The third is Sura Bang Yee Khan factory building which is the first international style built in Bangkok and Thonburi. 2) To study the transferring history of cultural heritage in historical area and nearby areas. The research methodology and equipment used in this study are 1) Interview experts and conduct a field study in historical area, 2) Ask experts or key informants to estimate significance and ability of old architecture, and 3) Inquire contentment and requirement from 400 people at cultural learning center by using questionnaires. The results of the study are 1) Old architecture can represent very interesting detail about history, culture, and knowledge of historical area (Thonburi), 2) All of the three buildings are worth and significant in using in different ways, 3) The presentation of culture should be presented by multimedia presentation from experience of local people in the study area, and 4) The cultural learning center should be built in the center of historical area to attract people to use it.